Knowledge Attitude and Practice of Covid-19 Preventive Measures among Pregnant Women Attending Antenatal Clinics in Kisumu and Siaya Counties - Ondieki, Everlyne Delylah (JOOUST, 2023)
Coronavirus (COVID-19) infection can lead to an increased risk of adverse pregnancy outcomes among pregnant women. To curb the spread of COVID-19, World health organization (WHO) recommended a series of preventive measures. However, the third wave persisted, and while the wave was tapering off, Kisumu and Siaya counties had a peak resurgence in the number of COVID-19 cases with a positivity rate of 28.4%. Knowledge, attitude and practice (KAP) studies are very useful in providing useful information about prevention and control measures. However, it was unknown whether pregnant women in Kisumu and Siaya counties, Kenya have a good knowledge, positive attitude toward COVID-19 preventive measures and taking precautions to avoid infection. This study determined the knowledge, attitude and practice of COVID-19 preventive measures among pregnant women attending antenatal clinics (ANC) in Kisumu and Siaya counties. The findings from this study will help provide information to guide in designing context specific information and education interventions to be provided during ANC visits. A concurrent mixed-methods study was conducted in Kisumu and Siaya Counties in western Kenya; a cross-section survey among 402 pregnant women attending ANC in 12 hospitals, four focused group discussions (FGDs) with 40 pregnant women and four key informants’ interviews (KIIs) among maternal and child health (MCH) clinic nurses. Ballot method of Simple random sampling was used to recruit women for the cross-sectional survey. Purposive sampling was used to select pregnant women for FGDs and nurses for KIIs. Correlation test was used to determine the correlation between knowledge, attitude and practice and data was plotted using a matrix plot, the distribution of continuous variables assessed using histograms, and the Shapiro-Wilk normality test. Pearson’s chi-square test was used to determine if there was a significant association between sociodemographic factors and knowledge, attitude and practices and multinomial logistics regression was used to determine predictors of knowledge, attitude and practice. Thematic analyses were used to describe qualitative findings. Of the 387 women interviewed, 98% (385/387) and 100% (387/387) had moderate and above scores in knowledge and attitude respectively and 23% had adequate practices. The matrix plot revealed a moderate correlation between knowledge and practice (R=0.3) and weak correlation between attitude and practice (R=0.2). Respondents age was significantly associated with knowledge (p=0.026) and attitude (p=0.042) and educational level was associated with knowledge, attitude and practice (p<0.05) in Pearson’s Chi-square test. Respondents from households with 3-5 and 6-8 members were 2.11 and 2.58 times likely to have poor practices, whereas respondents with tertiary level of education were 0.48 times less likely to have poor practices in multinomial logistics regression. The cost of face masks, smell of soaps, sanitizers and limited space were identified as barriers to COVID-19 prevention practices. Although pregnant women were aware of COVID-19 preventive measures, this did not translate into adequate COVID19 preventive practices. In Kenya, the government needs to implement measures to improve COVID-19 prevention practices, including COVID-19 vaccine uptake among pregnant women.
Keywords: Covid-19; Preventive Measures; Pregnant Women; Antenatal Clinics; Kisumu; Siaya County